2008
DOI: 10.1016/j.jcf.2007.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cystic fibrosis in five different states of Brazil as determined by screening of p.F508del, mutation at the CFTR gene in newborns and patients

Abstract: Cystic Fibrosis (CF) is one of the most common single-gene defects in European descent populations with an incidence of about 1 in every 2500 live births and carrier frequency of approximately 1 in 25. The most common mutation at the CF transmembrane conductance regulator (CFTR) gene is a deletion (p.F508del) of the phenylalanine codon 508; its frequency, however, is not the same throughout the world. The purpose of this paper is to document an application of a two-tier survey design in different states of Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
15

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 24 publications
3
41
0
15
Order By: Relevance
“…The G542X, R1162X, and N1303K mutations ΔF508 CFTR gene mutation was the most common mutation found in our study, which corroborates other reports from the same region of Brazil, (16,(22)(23)(24)(25) as well as international reports. (26,27) Other mutations of the CFTR gene, such as R1162X and N1303K, were less common in our CF patients, (22,24,28) as has been reported for CF patients in other parts of the world. (27) The frequencies of the GSTM1 and GSTT1 null genotypes in the CF patients in our study were similar to those found in healthy individuals, in Brazil (29) and elsewhere.…”
Section: Resultssupporting
confidence: 92%
“…The G542X, R1162X, and N1303K mutations ΔF508 CFTR gene mutation was the most common mutation found in our study, which corroborates other reports from the same region of Brazil, (16,(22)(23)(24)(25) as well as international reports. (26,27) Other mutations of the CFTR gene, such as R1162X and N1303K, were less common in our CF patients, (22,24,28) as has been reported for CF patients in other parts of the world. (27) The frequencies of the GSTM1 and GSTT1 null genotypes in the CF patients in our study were similar to those found in healthy individuals, in Brazil (29) and elsewhere.…”
Section: Resultssupporting
confidence: 92%
“…In Brazil, in view of the genetic diversity of the population (8,38), CF screening by searching for the F508del mutation would not be cost-effective, while searching for the more frequent mutations F508del, G542X, G551D, R553X, and N1303K would probably result in the detection of only one mutated allele and would not permit a diagnosis. On this basis, screening by genetic analysis would have to be planned to detect a larger number of mutations since, as is the case for regions of Southern Europe, especially Spain and Italy, only the search for at least 20 mutations would permit the detection of approximately 70% of affected individuals (9).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using a two-tier survey design in five Brazilians States (Minas Gerais, São Paulo, Paraná, Santa Catarina, and Rio Grande do Sul) suggested that nearly 48% of the CF alleles carry the F508del mutation and estimated that the disease incidence for Brazilians of European descent is 1 in 7576 live births. In addition, the investigators suggested that the CF prevalence in different parts of Brazil may differ by almost 20-fold (from 1 in 32,258 live births in São Paulo to 1 in 1587 in Rio Grande do Sul) (8).…”
mentioning
confidence: 99%
“…In Brazil, the frequency of this mutation, analyzed in the alleles of affected patients, varies from region to region: 49% in Rio Grande do Sul 21 27 . A recent study 22 analyzed the frequency of this mutation in European descendents in five Brazilian States (Minas Gerais, São Paulo, Paraná, Santa Catarina, and Rio Grande do Sul) and observed that approximately 48% of the alleles in CF patients carried the ΔF508 mutation and estimated the prevalence of the disease at 1:7,576 live births in European-descendant Brazilians. Due to the country's extensive miscegenation, the study also showed a large regional variation, estimating the mutation's prevalence at 1:32,258 in children born in the State of São Paulo and 1:1,587 in Rio Grande do Sul.…”
Section: Incidencementioning
confidence: 99%